Investigation on electronic and transport properties of two-dimensional Janus TiSiSeP2 monolayer using density functional theory - Võ, Thị Tuyết Vi; Nguyễn, Quang Cường; Nguyễn, Ngọc Hiếu (Hue University Journal of Science: Natural Science, 2023)
In this paper, the electronic and transport properties of two-dimensional (2D) Janus TiSiSeP2 monolayer were studied using density functional theory (DFT). The results exhibited that the Janus TiSiSeP2 monolayer is structurally stable and can be experimentally synthesized. At the ground state, the Janus TiSiSeP2 monolayer is an indirect semiconductor with a band gap of 1.23 eV at the hybrid functional HSE06 level. The electronic characteristics of TiSiSeP2 depend highly on an applied strain, expecially the band gap. Besides, the transport characteristics of TiSiSeP2 are also systematically investigated in the present work. Our findings contributed to a better understanding of the physical properties of 2D Janus TiSiSeP2 monolayer.